(untitled) (Research, Society and Development, 2024)
The aim of this study was to evaluate the antifungal activity and cytotoxicity of the plant extract from Camellia sinensis (green tea) in vitro, as well as to assess the antifungal effect of amphotericin B and fluconazole on 22 strains of Candida spp. isolated from the oral cavity of HIV-positive patients. The minimum fungicidal concentration (MFC) and minimum inhibitory concentration (MIC) were determined in planktonic cells using serial dilutions of green tea extract and antifungals. After determining the extract concentration at MIC and MFC, biofilm was prepared for each strain. Cytotoxicity in mouse macrophages (RAW 264.7) was evaluated to assess the cellular viability of this substance. Colony-forming units (CFU/mL) were counted, and the data were statistically evaluated using the Mann-Whitney test (p<0.05) for biofilm, visual observation for MIC and MFC, and ANOVA and Tukey for cytotoxicity. The results demonstrated viability of green tea extract in the analyzed cells. It was concluded in this study that C. sinensis (green tea) extract showed antifungal activity in planktonic cells and in biofilm for all Candida strains evaluated, with no cytotoxic effects on RAW 264.7. Fluconazole exhibited fungicidal effect in planktonic cells, while amphotericin B showed antifungal effect on C. albicans strains and microbial resistance in non-albicans strains.